Structural-property relationships in metal halide like-perovskites under extreme conditions - Rodríguez Hernández, Juan Simón (2023)
Metal halide perovskites are versatile materials with numerous promising applications in solar cells, semiconductors, electronic devices, and optoelectronic performance. Studying reveals interesting and important physical properties that are strongly related to the pressure/temperature-induced modifications on their crystal lattice and structural phase transitions. For example, the Erythrosiderite-halides complexes, such as A 2 FeCl 5 .H 2 O with A = Cs, Rb, K or NH 4 , exhibit at room temperature an orthorhombic structure Pnma or Cmcm The Cs 2 FeCl 5 .H 2 O ( Cmcm ) at Tt = 156 K undergoes a structural phase transition (SPT) to a monoclinic (C2/c) structure that could be related to the ferroelastic mmmmF2/m type. The strains in the sample were analy z ed based on Landau theory and using Raman spectroscopy. The results define a new ferroic order in the sample. Other like perovskites with the general formula ABABX3 can be described by the most common space group P63/mcc. The hybrids based on dimethylammonium [(CH3)2NH2]+, such as DMAPbX3 with halide ions X = Br or I, undergo a structural phase transition at Tt = 250 K via an order disorder mechanism. At low temperatures, t he strong electron phonon coupling permits self trapped exciton states, modifying the photoluminescence (PL) profile and increasing new band contributions and a n emission change of the PL from orange red to bright red. A thermochromic effect is also observ ed in DM DMAPbI3 after Tt. CsCuCl3, with the same P63/mcc crystal structure, was studied at low temperatures and high pressure, and spin phonon coupling (SPC) was verified with decreasing temperature. A paramagnetic to antiferromagnetic phase transition permits the SPC effect, but an anomalous phenomenon was identified at T = 15 K . At high pressure, a structural phase transition to C 2 was found , and the bulk modulus sample for each phase was calculated, indicating potential applications for the compound. The investigation revealed that the SPT involves the reorganization of the internal [CuCl 6 4 octahedra, with Cl Cu Cl bending contributing more than Cl Cu Cl stretchings . In this context, the results of the structural proper ty relations in past metal halide like perovskites pave the way for developing new and improved devices and technologies.